Relationship Between Shear Wave Elastography Findings and Histologic Prognostic Factors of Invasive Breast Cancer. Issue 1 (March 2020) - Gemici, Aysegul Akdogan; Ozal, Safiye Tokgoz; Hocaoglu, Elif; Inci, Ercan
Abstract : Objective: Shear wave elastography (SWE) is an adjunct to grayscale ultrasound examinations for evaluating breast masses. This study aimed to determine the SWE features that correlated with prognostic parameters for breast cancer. Methods: Between January 2018 and May 2018, 80 patients who were confirmed to have invasive cancers by core-needle biopsy and who were scheduled for surgery were imaged using B-mode ultrasound and SWE. Measurements were taken from a region of interest positioned over the stiffest part of the peripheral zone and mass. Three measurements were taken, and the average of the mean stiffness value was used for analysis. Results: The mean tumor size, elasticity value of tumors, and elasticity of the peripheral zone were 2.9 ± 1.48 cm (range, 0.6–8 cm), 154.8 ± 8.55 kPa (range, 116.25–179 kPa), and 171.34 ± 5.22 kPa (range, 150.95–182.43 kPa), respectively. The types of breast cancer included were invasive ductal carcinoma (n = 71 [88.75%]; 69 invasive ductal carcinoma not otherwise specified, 1 solid papillary carcinoma, and 1 invasive micropapillary carcinoma), invasive lobular carcinoma (n = 2 [2.5%]), mixed invasive ductal and lobular carcinoma (n = 4 [5%]), mucinous carcinoma (n = 2 [2.5%]), and metaplastic cancer (n = 1 [1.25%]). A strong correlation was found between mean elasticity values and tumor grade ( P = 0.018) and between mean elasticity values and lymphovascular invasion (LVI) positivity ( P = 0.008). There were no significant differences between SWE values and tumor diameter or between histological tumor characteristics and SWE. Conclusions: We found that some clinicohistopathologic features of poor prognosis had higher elasticity values than those of favorable prognosis.